Quantitative dynamic optical coherence tomography by multi-time-window signal intensity variance - Rion Morishita; Ibrahim Abd El-Sadek; Pradipta Mukherjee; Tanatchaya Seesan; Yiheng Lim; Tomoko Mori; Atsuko Furukawa; Satoshi Matsusaka; Shuichi Makita; Yoshiaki Yasuno (My University, 2024)
Dynamic optical coherence tomography (DOCT) is a method to visualize intratissue activities by analyzing the time sequence of OCT images. We previously established two DOCT contrasts, logarithmic intensity variance (LIV) and late OCT correlation decay speed (OCDSl), and applied them to several medical and pharmaceutical studies. However, these DOCT contrasts have two problems, which are a measurement time dependency of LIV and a difficulty of interpretation of OCDSl. Here we present a new DOCT algorithm which solves these two problems. The new method first computes several LIV values with multiple time window sizes. This LIV shows a monotonically increasing saturation curve. The saturation level and saturation speed, which are named authentic LIV (ALIV) and swiftness, are obtained by fitting the LIVs with a saturation function. Numerical simulation revealed that ALIV is sensitive to the occupancy of the dynamic scatterers over all dynamic and static scatterers, while swiftness is sensitive to the speed of the dynamic scatterers. According to the principle and experimental results using tumor spheroids, ALIV and swiftness are more quantitative and easier to interpret than our previous DOCT methods.
Keywords: Optical Coherence Tomography Applications; Advanced Fluorescence Microscopy Techniques; Photoacoustic and Ultrasonic Imaging